SUPERVISI AKADEMIK KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI SMP KATOLIK BUNDA HATI KUDUS WOLOAN - Fecky Evendy Singal; Gloria Theresia Motoh; Sefanya Anyaka Jovanka Datu; Enjelina Tresia Kalalo (Lembaga Penelitian STKIP Widya Yuwana, 2026)
The purpose of this research is to describe the Principal's Academic Supervision in Improving Teacher Performance at Mother of Sacred Heart Catholic Junior High School Woloan. The research method used in the preparation of this thesis is descriptive-qualitative approach. Data sources consist of one principal and teachers at Mother of Sacred Heart Catholic Junior High School Woloan. Collection techniques include observation, interview, and documentation. The collected data were then analyzed through the following steps: data reduction, data presentation and data verification. The results showed that principals actively carry out academic supervision through several stages, namely supervision planning, implementation of classroom observations, and follow-up in the form of coaching. Supervision is carried out in a structured manner and uses a nurturing and dialogical approach. Supporting factors for the implementation of supervision include the communicative leadership of the principal, teacher support and a positive work climate. Meanwhile, the inhibiting factors include internal factors of teachers in terms of self and administrative readiness in the implementation of supervision. The principal's development efforts in academic supervision to improve teacher performance in implementing academic supervision include systematic supervision planning, direct classroom observation, providing constructive feedback, and follow-up in the form of coaching and training such as In-House Training (IHT).